The Use of Fillers by the Students of English Study Program in English Speaking Practice - Yulpia, Tika (Jurnal Pendidikan Dasar dan Menengah, 2025)
This study examines the use of fillers in speech among students in the Intermediate English-Speaking class at Palangka Raya University during the 2023/2024 academic year. Fillers, which include words, phrases, and clauses that do not carry meaning but serve to fill pauses, play a role in communication by organizing thoughts and managing speech flow. The research aims to classify the types of fillers used and determine which type is most dominant. Using a qualitative descriptive method with content analysis, data were collected through documentation and analyzed based on Rose’s (1998) theory. From 32 recorded speech samples, a total of 306 fillers were identified. The findings revealed that Unlexicalized Fillers (such as "uh" or "um") were overwhelmingly dominant, accounting for 93.8% (287 instances), while Lexicalized Fillers (such as "you know" or "I mean") constituted only 6.2% (19 instances). The results suggest that excessive filler usage indicates a lack of fluency, as students spoke spontaneously without prior preparation. While fillers can aid communication, their overuse may hinder clarity. These findings contribute to sociolinguistic research, emphasizing the need for training to reduce filler dependency and improve spoken fluency in English learners.